There are two approaches to this problem - we can solve it directly, or we can examine the answer choices and come to a conclusion about which one must be correct.

Algebraic approach:

Draw a perpendicular from point A to side BC, label it point D. Draw another perpendicular from point B to side AC, label it point E. Now we have a 30-60-90 triangle and a two similar 15-75-90 triangles. Let the length of CD = a

Attachment:

Isosceles Triangle.png [ 4.68 KiB | Viewed 30124 times ]
Now we can use some ratios to figure out x

Looking at triangle ABD, we know that \(\frac{BD}{AB} = \frac{x-a}{x} = \frac{\sqrt{3}}{2}\) (1)

And looking at triangles ADC and BEC (similar triangles) we can see that \(\frac{AC}{DC} = \frac{BC}{EC} = \frac{2\sqrt{2}}{a}=\frac{x}{\sqrt{2}}\) (2)

From (2) \(ax = 4\), or \(a=\frac{4}{x}\)

Cross multiply (1) and plug in \(a=\frac{4}{x}\)

\(2x-2a = \sqrt{3}x\)

\(2x-2(\frac{4}{x})=\sqrt{3}x\)

\(2x-\frac{8}{x}-\sqrt{3}=0\) --> multiply by \(x\)

\(2x^2-8-\sqrt{3}x^2=0\) --> gather terms

\((2-\sqrt{3})x^2=8\)

\(x=\sqrt{\frac{8}{2-\sqrt{3}}}\) --> Now this doesn't look like any of our answer choices, so we will have to manipulate it a bit

\(x=\frac{2\sqrt{2}}{\sqrt{2-\sqrt{3}}}\) --> multiply top and bottom by the conjugate of the denominator to rationalize the denominator

\(x=\frac{2\sqrt{2}*\sqrt{2+\sqrt{3}}}{(\sqrt{2-\sqrt{3}})*(\sqrt{2+\sqrt{3}})}\)

\(x=\frac{2\sqrt{2}*\sqrt{2+\sqrt{3}}}{1}\) --> bring the \(\sqrt{2}\) into the square root

\(x=2\sqrt{4+2\sqrt{3}}\) --> Now rearrange the expression to complete the square within the square root

\(x=2\sqrt{1+2\sqrt{3}+3} = 2\sqrt{(1+\sqrt{3})^2}\)

\(x=2(1+\sqrt{3})\)

Answer: E

WHEW! Ok, now the simpler approach that involves almost no calculation, just a few quick estimates and a good idea of what's going on in the triangle:

Because \(\angle{B}\) is \(30^{\circ}\), and the side opposite \(\angle{B}\) is \(2\sqrt{2}\), we know that the other two sides, x, will be longer than \(2\sqrt{2}\).

\(2\sqrt{2}\) is \(\approx 2.8\)

Now if we look at the answer choices:

(A) \(\sqrt{3}-1 \approx 0.73\)

(B) \(\sqrt{3}+2 \approx 3.73\)

(C) \(\frac{\sqrt{3}-1}{2} \approx 0.36\)

(D) \(\frac{\sqrt{3}+1}{2} \approx 1.36\)

(E) \(2(\sqrt{3}+1) \approx 5.46\)

Immediately we can eliminate A, C and D. To choose between B and E, we need to ask whether x should be almost twice as much as AC, or less than 1.5*AC. Go back to the diagram and look at triangle ABD. Since it is a 30-60-90 triangle, we know that AB (i.e. \(x\)) = 2*AD. Now, though the diagram is not to scale, it is accurate enough to surmise that AD is only slightly less than AC. Therefore, \(x\) should be only slightly less than 2*AC, which matches with answer E.

I recommend the second approach, but it only works well because the answer choices are spread out enough. That being said, I don't think the GMAT will expect you to do the algebraic approach, and will design the answer choices specifically to be able to use approximation.

Cheers

_________________

Dave de Koos

GMAT aficionado